Enhancing Oral Tradition in Fiji for the Study of Archaeological Remains. The Case of the Hillforts in the Nadroga-Navosa Province - Loredana, Lancini; Duval-Gatignol, Hervé; Nunn, Patrick; Compatangelo-Soussignan, Rita; Nakoro, Elia; Tokainavatu, Nikolau (Studia mythologica Slavica, 2025)
The Fiji Islands offer a compelling case for cross-cultural research integrating archaeology and oral tradition. Fijian society still practices oral transmission, preserving diverse stories with cultural significance. Many legends and beliefs are tied to past settlements, considered sacred due to their symbolic role. In June 2022, fieldwork in Nadroga-Navosa (Viti Levu) as part of the Environmental Changes and Heritage in the Fijian Islands project, explored hillforts and oral traditions through archaeological surveys. Findings from sites like Tabuqutu and Old Tau reveal that landscapes and remains are deeply embedded in local memory. Stories of origins, place names and beliefs about hillforts as ancestral homes highlight the enduring role of oral tradition in shaping historical knowledge. This paper presents these findings, emphasizing the value of oral tradition in interpreting archaeology within Fijian society.